Spectral Analysis of the Bounded Linear Operator in the Reproducing Kernel Space W2m(D) - Lihua Guo; Songsong Li; Boying Wu; Dazhi Zhang (The Scientific World Journal)
We first introduce some related definitions of the bounded linear operator L in the reproducing kernel space W2m(D). Then we show spectral analysis of L and derive several property theorems.